Расположите числа в порядке убывания √2;∛3;[latex] \sqrt[6]{5} [/latex] вычислить [latex]27 \frac{1}{3} -( \frac{1}{2} ) -^{2} [/latex];[latex] \sqrt[4]{1296} + \sqrt[3]{-0.064} [/latex]; решите уравнения [latex] \sqrt[5]{-2 x...
Расположите числа в порядке убывания √2;∛3;[latex] \sqrt[6]{5} [/latex]
вычислить [latex]27 \frac{1}{3} -( \frac{1}{2} ) -^{2} [/latex];[latex] \sqrt[4]{1296} + \sqrt[3]{-0.064} [/latex];
решите уравнения [latex] \sqrt[5]{-2 x-5} =-2[/latex];[latex] \sqrt[6]{x2-2x+61} =2[/latex]
Ответ(ы) на вопрос:
[latex]\sqrt[3]3>\sqrt2>\sqrt[6]5[/latex]
[latex]27\frac{1}{3}-\frac{1}{2}-2=26\frac{8}{6}-\frac{3}{6}-2=24\frac{5}{6}\\\sqrt[4]{1296}+\sqrt[3]{-0,064}=\sqrt[4]{16\cdot81}+\sqrt[3]{\frac{-64}{1000}}=\sqrt[4]{2^4\cdot3^4}-\sqrt[3]{\frac{4^3}{10^3}}=\sqrt[4]{(2\cdot3)^4}-\sqrt[3]{(\frac{4}{10})^3}=2\cdot3-0,4=5,6[/latex]
[latex]\sqrt[5]{-2x-5}=-2\\(\sqrt[5]{-2x-5})^5=-2^5\\-2x-5=-32\\2x=27\\x=13,5\\\\\sqrt[6]{x^2-2x+61}=2\\(\sqrt[6]{x^2-2x+61})^6=2^6\\x^2-2x+61=64\\x^2-2x-3=0\\(x-1)^2-1-3=0\\(x-1)^2=4\\|x-1|=2\\x-1=2\lor{x-1}=-2\\x=3\lor{x}=-1[/latex]
для: х=3 i х=-1 [latex]x^2-2x+61\geq0[/latex]
Не нашли ответ?
Похожие вопросы